Photo-assisted SCR over highly dispersed silver sub-nanoparticles in zeolite under visible light: An Operando FTIR study. (1st September 2019) - Hamoud, Houeida Issa; Lafjah, Mama; Douma, Fatima; Lebedev, Oleg I.; Djafri, Fatiha; Valchev, Valentin; Daturi, Marco; El-Roz, Mohamad
Abstract: In this study, the photo-assisted SCR-NH3 activities of vanadium containing zeolite X (ZX-V) and Ag@ZX-V catalysts are investigated under visible-light and soft temperature conditions (RT and T = 150 °C). The highly dispersed silver was incorporated into the zeolite structure as Agn δ+ nano and sub-nano-clusters with small particle size using a new photochemical concept. The catalysts were characterized using different techniques such as XRD, N2 sorption, H-TEM, and DR–UV–Vis. An in situ FTIR study of adsorbed CO was also performed for the characterization of the metal sites and their accessibility. The catalytic reaction was investigated using the operando FTIR technique allowing the study of both Ag@ZX-V and ZX-V catalytic surfaces, and the gas phase of the reaction in real time. Both catalysts are not active in dark and only Ag@ZX-V exhibits a photocatalytic activity under visible light. At RT, the results show that silvers clusters promote the photocatalytic oxidation of NH3 /NO, and no SCR is observed. This probably due to an energy transfer from the metallic site to the triplet oxygen and the formation of highly oxidant singlet oxygen. However, at T = 150 °C a significant photo-assisted SCR activity is observed under visible light irradiation with more than 18% of additional NOx removal. The different behavior of the material at 150 °C in respect to its activity at RT is mainly attributed to the additional formation of silver nanoparticles and to the possible formation and conversion of intermediates that are not formed and or converted at RT (thermodynamic limitation). Basing on this study, a possible mechanism of the photo-assisted SCR reaction over Ag@ZX-V catalyst is proposed.